Вы находитесь на странице: 1из 4

MATH4052 Supplementary Exercise 1

14 November, 2011
Problem 1. Solve the following diffusion equation

ut uxx = et x > 0, t > 0
u(x, 0) = cos x x>0

ux (0, t) = 0 t>0
R
Hints: S(, ) d = 1 and cos = Re(ei ).
Solution
Let w(x, t) be the even extension of u(x, t) about the point x = 0, then w satisfies the system

wt wxx = fe (x, t) x R, t > 0
w(x, 0) = e (x) xR
where
   
et x>0 cos x x>0
fe (x, t) = = et and e (x) = = cos x
et x<0 cos(x) x < 0
Using the formula for diffusion equation
Z Z tZ
w(x, t) = S(x y, t)e (y) dy + S(x y, t s)fe (y, s) dy ds
0

The first integral is


Z Z
S(x y, t)e (y) dy = S(x y, t) cos y dy


Z 
1 (xy)
2
iy
= Re e 4t e dy
4t
 Z   
1 y 2 2(x + 2it)y + x2
= Re exp dy
4t 4t
 Z   
1 [y (x + 2it)]2 + 4t2 4ixt
(completing square) = Re exp dy
4t 4t
 Z   
1 [y (x + 2it)]2
= Re et+ix exp dy
4t 4t
 Z 
1 2
(let = y (x + 2it)) = Re et+ix e 4t d
4t
 Z 
= Re et+ix S(, t) d

 
= Re et+ix = et cos x
For the source term,
Z tZ Z tZ
S(x y, t s)fe (y, s) dyds = S(x y, t s)es dyds
0 0
Z t Z
= es S(x y, t s) dy ds
0
Z t Z
(let = x y) = es S(, t s) d ds
0
Z t
= es ds = 1 et
0
So,
u(x, t) = w(x, t)|x>0 = 1 et + et cos x

1
Problem 2. Solve the following system of equations

1 x R t (0, 1)
ut uxx =

 0 xR t1
1 |x| 1
u(x, 0)=

0 |x| > 1

Express the result in terms of Erf(z).


Solution
Using the formula for diffusion equation
Z Z tZ
u(x, t) = S(x y, t)(y) dy + S(x y, t s)f (y, s) dy ds
0

where
 
1 y R, s (0, 1) 1 y [1, 1]
f (y, s) = and (y) =
0 y R, s 1 0 y (, 1) (1, )

The first integral is


Z Z 1 Z 1 Z 
S(x y, t)(y) dy = + + S(x y, t)(y) dy
1 1
Z 1 Z 1
1 (xy)2
=S(x y, t)(1) dy = e 4t dy
1 4t 1
  Z x1
xy 1

4t 2
let p = = ep ( 4tdp)
4t 4t x(1)

4t
x+1
Z Z x+1 Z x1 !
1 1

4t 4t 4t
p2 2
= e dp = ep dp
x1 0 0
 4t   
1 x+1 1 x1
= Erf Erf
2 4t 2 4t
For the source term, there are two cases to be considered, namely t 1 and t (0, 1).
1. t 1 s (x, t)
6 r
f (y, s) = 0

1
f (y, s) = 1
-y
O
Z tZ Z 1 Z t Z
S(x y, t s)f (y, s) dy ds = + S(x y, t s)f (y, s) dy ds
0 0 1
Z 1Z
= S(x y, t s)(1) dy ds
0
Z 1 Z
(let q = x y) = S(q, t s) (dq) ds
0
Z 1Z
= S(q, t s) dq ds
0
| {z }
1
Z 1
= ds = 1
0

2
2. t (0, 1) s
6
f (y, s) = 0
1
r
(x, t) f (y, s) = 1
-y
O
Z tZ Z tZ
S(x y, t s)f (y, s) dy ds = S(x y, t s)(1) dy ds
0 0
Z t Z
(let q = x y) = S(q, t s) (dq) ds
0
Z tZ
= S(q, t s) dq ds
0
| {z }
1
Z t
= ds = t
0

So,    
1 x+1 1 x1

Erf Erf +1 t>1
2
2 t 2 2 t
u(x, t) =    

1 x+1 1 x1

Erf
Erf +t t (0, 1)
2 2 t 2 2 t

Problem 3. Solve the following wave equation



utt 4uxx = 0 x (0, ), t > 0


u(x, 0) = 0
x (0, )
ut (x, 0) = 0 x (0, )

u(0, t) = 1

t>0

u(, t) = t t>0
Solution
As the boundary conditions of the given system are not zero, we should apply the subtraction
x0 x(1t)
method, let w(x, t) = u(x, t) 0 t x
0 1 = u(x, t) + 1, then w(x, t) satisfies

wtt 4wxxx = 0 x (0, ), t > 0


w(x, 0) = 1
x (0, )
wt (x, 0) = x x (0, )



w(0, t) = 0 t>0

w(, t) = 0 t>0

Since the boundary conditions for w(x, t) are zero, w(x, t) can be solved by separation.
Let v(x, t) = X(x)T (t) be the separated solution that satisfies

vtt 4vxx = 0 x (0, ), t > 0
v(0, t) = 0 t>0

v(, t) = 0 t>0

Substituting v(x, t) = X(x)T (t) into vtt 4vxx = 0 yields


T X
= =
4T X
where is a constant (eigenvalue) to be determined.

3
Furthermore, substituting v(x, t) = X(x)T (t) into the boundary conditions gives
X(0) = X() = 0
To determine the values of , we need to solve the spatial system

X (x) + X(x) = 0 x (0, )
X(0) = X() = 0
and the following three cases have to be considered separately.

1. If > 0, let = > 0, then the solutions are of the form
X(x) = c1 ex + c2 ex
But X(0) = X() = 0 forces c1 = c2 = 0, so this case is rejected as it gives out trivial
solution X(x) = 0.
2. If = 0, the differential equation becomes X (x) = 0, then the solution is
X(x) = ax + b
But X(0) = X() = 0 forces a = b = 0, so this case is also rejected.

3. If > 0, let = > 0, then the solutions are of the form
X(x) = C cos x + D sin x
The boundary conditions X(0) = X() = 0 gives
X(0) = C = 0 and X() = D sin = 0
For a non-trivial solution, we require D 6= 0, which forces = n = 1, 2, 3, .
The solutions to the corresponding temporal system T (t) + 4n2 T (t) = 0 are of the form
T (t) = A cos 2nt + B sin 2nt

Thus, the solution for w(x, t) is given by



X
w(x, t) = (An cos 2nt + Bn sin 2nt) sin nx
n=1

The constants An s and Bn s can be found by the initial conditions of w:


R x 
x X
0 R
1 sin nx dx
1 = w(x, 0) = An sin nx = An =
n=1 0
sin2 nx dx
 
1 1 1
= sin nx x cos nx + cos nx
n2 n n 0 2
2
=
n
R 
x X
0 x sin nx dx
= wt (x, 0) = 2nBn sin nx = Bn = R
n=1
2n 0 sin2 nx dx
 
1 1
= 2 sin nx + x cos nx n
n n 0
cos n (1)n
= = 2
n2 n
So the solution to the system in u is
 
x(1 t) 1 X (1)n 2
u(x, t) = 1 + sin 2nt cos 2nt sin nx
n=1 n2 n